Perlindungan dan Pemanfaatan Cagar Budaya Berbasis Partisipasi di Kota Metro dalam Perspektif Undang-Undang Nomor 11 Tahun 2010 Tentang Cagar Budaya - Kurniawan, Ganda; Latif, Abdul; Pratiwi, Siswantari (IAI Nasional Laa Roiba Bogor, 2025)
The protection and use of cultural heritage as part of building national character is actually not something new in Indonesia. In order to preserve cultural heritage, Law Number 11 of 2010 concerning Cultural Heritage was issued. However, a number of problems related to cultural heritage still continue to occur in various regions in Indonesia. This research is qualitative research with a normative approach. Data was obtained from primary, secondary and tertiary legal materials which were then analyzed interpretively. The results of this research conclude that first, legal protection in the protection and use of cultural heritage is very important because it is the basis for regulations regarding the management of cultural heritage and related aspects. Arrangements for problems that arise and resolution of disputes related to cultural heritage are regulated in Law Number 10 of 2010 concerning Cultural Heritage. Preventive legal protection provides an opportunity to raise objections while repressive legal protection aims to resolve disputes and is used to resolve disputes. Second, the protection and use of cultural heritage in Metro City has been going well and is in line with the spirit of Law Number 10 of 2010 concerning Cultural Heritage. Aspects of public participation have appeared in the implementation and benefit-taking processes. This grows in line with the commitment and role of the government which has a direct impact on increasing awareness and participation of stakeholders in the protection and use of cultural heritage. This is demonstrated by the presence of the Cultural Heritage Expert Team, Regional Regulations and Mayor's Regulations related to Cultural Heritage, including local curriculum related to history and Cultural Heritage in the Elementary and Middle School curriculum as well as providing compensation for reduced Land and Building Tax (PBB) to cultural heritage owners.